HUMOR DALAM MAJALAH DJAKA LODANG (Kajian Bentuk Humor) - Siti Mulyani (LITERA, 2005)
The use of puns to express humor in Djaka Lodang, a Javanese magazine, is alanguage phenomenon of language use that is interesting to study. This researchstudy aims to (1) describe sections containing humorous discourses in Djaka Lodang,and (2) describe the forms of the humorous discourses.This study employed the descriptive approach. The data sources were DjakaLodang published in the period of January to March 2003. The research data weresegments of discourse containing humorous elements. The data were collectedby reading and recording by means of the discourse analysis technique. The datavalidity was assessed through semantic validity. The data reliability was assessedby reading and rereading (intra-rater reliability). The data were analyzed by usingthe descriptive technique comprising induction and comparison, categorization,tabulation, and inference making.The research findings show that of 32 sections available in Djaka Lodang 18sections contain humorous discourses. The 18 sections are (1) Cerita Rakyat, (2)Srumuwus, (3) Wawasan Droning Negara, (4) Wawasan Jaban Ranglcah, (5) Pagelaran,(6) Profil, (7) Sketsa, (8) Pedhalangan, (9) Lem bar Agama, (10) Macapat, (11) Seninjong,(12) Cerita Sambung, (13) Mendhowan, (14) Pengalamanku, (15) Cerita Cekak, (16) WacanBocah, (17) Tetepungan, and (18) Dhat Nyeng. There are seven forms of the humorousdiscourses, namely description, story, topic sentence, poem, magic spell, trappingexpression, and pun.